Low‐level laser therapy promotes the osteogenic potential of adipose‐derived mesenchymal stem cells seeded on an acellular dermal matrix1. Issue 6 (26th March 2013) - Choi, Kyuseok; Kang, Byung‐Jae; Kim, Hyoju; Lee, Seungmin; Bae, Sohee; Kweon, Oh‐Kyeong; Kim, Wan Hee
Abstract: This study investigates the feasibility of using an adipose‐derived mesenchymal stem cell (ASC)‐seeded acellular dermal matrix (ADM) along with low‐level laser therapy (LLLT) to repair bone defect in athymic nude mice. Critical‐sized calvarial defects were treated either with ADM, ADM/LLLT, ADM/ASCs, or ADM/ASCs/LLLT. In micro‐computed tomography scans, the ADM/ASCs and the ADM/ASCs/LLLT groups showed remarkable bone formation after 14 days. Additionally, bone regeneration in the ADM/ASCs/LLLT group was obvious at 28 days, but in the ADM/ASCs group at 56 days. Bone mineral density and bone tissue volume in the ADM/ASCs/LLLT group significantly increased after 7 days, but in the ADM/ASCs group after 14 days. Histological analysis revealed that the defects were repaired in the ADM/ASCs and the ADM/ASCs/LLLT group, while the defects in the ADM and the ADM/LLLT groups exhibited few bone islands at 28 and 56 days. The successful seeding of ASCs onto ADM was confirmed, and LLLT enhanced the proliferation and the survival of ASCs at 14 days. Our results indicate that ASC‐seeded grafts promote bone regeneration, and the application of LLLT on ASC‐seeded ADM results in rapid bone formation. The implantation of an ASC‐seeded ADM combined with LLLT may be used effectively for bone regeneration. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.